Solid-state chelates of ethylenediamine-tetraacetate with alkali earth metals - Moitinho, ABS; Ionashiro, E. Y.; de Souza, G. R.; Fertonani, F. L. (Kluwer Academic Publ, 2004)
Solid-state M-EDTA chelates, where M represents the divalent ions Mg(II), Ca(II), Sr(II) or Ba(II) and EDTA is ethylenediaminetetraacetate anion, were synthesized. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC) and X-ray diffraction powder patterns have been used to characterize and to study the thermal behaviour of these chelates. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition.
Keywords: alkali earth metals; EDTA; thermal behaviour